Python Everything about Python programming - Donaldson Toby (San Francisco, Peachpit Press, 2014)
Python is a remarkably powerful dynamic programming language used in a wide variety of situations such as Web, database access, desktop GUIs, game and software development, and network programming. Fans of Python use the phrase "batteries included" to describe the standard library, which covers everything from asynchronous processing to zip files. The language itself is a flexible powerhouse that can handle practically any application domain. This task-based tutorial on Python is for those new to the language and walks you through the fundamentals. You'll learn about arithmetic, strings, and variables; writing programs; flow of control, functions; strings; data structures; input and output; and exception handling .
Languages de script (Informatique)
Beginners